Laurier: "Le depute de Quebec-Est" - Williams, Garth (University of Ottawa (Canada), 2004)
This thesis adopts a social-cultural approach to the history of politics to explain contradictions in the "Laurier legend" and connect social and political history traditions. It argues Laurier is best understood as the representative of Quebec-Est where he engaged in the social-cultural work of politics, linking citizens to their government. Quebec-Est guided him consistently. It was an urban, working-class, commercial and industrial, French Canadian Catholic riding, devastated by economic decline in the mid-nineteenth century. This social and economic context reduced the immediacy of national conflicts over language and religion and encouraged compromise, to secure government resources needed to renovate the port, bridge the St. Lawrence, build a railway to the west and regain the city's "rightful" place in Canada. It fostered a political culture characterized by intense partisanship, personal accountability and broad public interest in local businesses---including their labour disputes. When Laurier was first elected, Quebec-Est had relatively close-knit business and social networks. As it grew, social relations became more structured, impersonal, and a greater range of activities reduced public space for politics while the Church successfully resisted and adapted to these modern trends, regaining local influence. The thesis traces this evolution through changes in the instruments for shaping and expressing public opinion that connected Laurier to Quebec-Est: the Liberal party, the party newspaper, election campaigns and patronage. Much was expressed through conflict between two factions: 'les vrais liberaux,' organized around pre-existing personal networks of businessmen and labourers, and 'les parentistes,' a more impersonal organization of larger, more conservative, businessmen structured around patronage. When, one, or both, held sway, Laurier fulfilled the riding's ambitions. When they fought, he could address other concerns. A definitive 'vrai liberal' victory over 'les parentistes' in 1906 deprived Laurier of a disciplined organization for patronage distribution, encouraging him to rationalize the civil service and newspaper management. He remained loyal to the party, but it had become disconnected from the larger manufacturers, Catholic labour unions and Church organizations with growing influence in the riding. The party's new structure and Laurier's reforms explain his defeat in 1911; he even---very nearly---lost his seat that year.
Keywords: Biography.; History, Canadian.